Characterization of the Microbial Landscape of the Intestine in Infants - Residents of Areas with Significant Anthropogenic Impact and Ways of Correction of Detected Disorders - Yu.G. Reznichenko; M.O. Yartseva; O.M. Kamyshny (Zaslavsky O.Yu., 2012)
The examination of 107 children in the first year of life - residents of large industrial cities and 184 children from mid-sized cities has been carried out. It is proved that more significant dysbiotic disorders that are characterized by decrease in the amount of normal symbionts and increase the number of opportunistic pathogens in the gut are detected in children who live in ecologically unfavorable regions are. The necessity of prophylactic use of probiotics to mitigate the impact of living in an industrial city in impossibility of breastfeeding was substantiated.